A Cross-sectional Survey of the Willingness of Tertiary Hospital Staff to Donate Blood in Sagamu, Nigeria - Jeminusi OA; Ojo OT; Adegoke OM; Alabi AA; Sholeye OO; Olatunji PO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2016)
Background: Available donor blood rarely meets the demand in sub-Saharan Africa due to obstacles to blood donation. Willingness to donate blood is adjudged an important step to the actual practice of donating blood. Objective: To assess the willingness of the members of staff of the hospital to donate blood and determine factors affecting their willingness or otherwise. Methods: This was a descriptive cross-sectional study. A proportional allocation of participants was carried out at the various departments in the hospital using self-administered questionnaire. Results: Overall, 183 (73%) of the 246 respondents expressed willingness to donate blood, 111(45%) of whom have been asked to donate blood in the past. Only 91(37%) had donated blood in the past. Significantly higher proportion of health staff showed the willingness to donate blood generally and voluntarily compared to non-health staff. Significantly higher proportion of respondents with tertiary education showed the willingness to donate blood. Two hundred and eighteen (88.8%) were willing to donate blood to help the patient in need while fear of exposure to HIV infection, needle prick and dizziness constituted the major factors discouraging blood donation (19.9%, 18.7% and 18.3% respectively). Conclusion: Willingness to donate blood was mostly based on the primordial motivation of helping the patient in need which does not translate to blood donation. There is a need to improve awareness and advocacy on blood donation among hospital staff and the general population.